A cumulação dos adicionais de insalubridade e periculosidade, sob a perspectiva constitucional e internacional, como proteção jurídica à saúde do trabalhador - Talyuli Júnior, Ely (2018)
This dissertation addresses the issue of the possibility of cumulation of the additional of insalubrity and hazardousness by the employee. Firstly, considerations were given to the working environment and the modern legal protection afforded by doctrine, and by national and international legislation, to the health of the worker. Then, characteristics of the additional were described. The confirmation of the right to simultaneous perception continued with research based on contemporary constitutional law, the reinterpretation of current labor legislation, doctrinal perceptions and the examination of the precedent that was based on the current understanding by the Superior Labor Court. In order to strengthen the thesis of the applicability of international conventions as international human rights treaties, its reception in both domestic law and comparative law has been deepened. In the end, it was evidenced that the additional remuneration are human rights of the worker safeguarded by the constitutional norms and the international norms incorporated to the Brazilian legal order. Together with the safe and healthy working environment, the additional ones interwine with the fundamental purpose of reducing the inherent risks of work and of realizing the ideal of social justice.